Facts about Wildlife Diseases: SARS-CoV2 in white-tailed deer - Samantha M Wisely (EDIS)
SARS Cov2, the virus that causes COVID-19, has been discovered in white-tailed deer. This publication provides information to the general public, hunters, and deer farmers as to what SARS CoV2 is, the evidence for COVID-19 in deer, and if people can get COVID-19 from deer.